Tinjauan Yuridis Pelaksanaan Perjanjian Ekstradisi Indonesia-Malaysia (Studi Kasus: Djoko Soegiarto Tjandra) - Nuban, Julio Benyamin; Kase, Dhesy A; Tukan, Elisabeth N S B (Law Faculty, Nusa Cendana University, 2024)
Corruption is a complex and common problem faced by all countries. It's about the side effects of corruption that can shake up a country's life. Extradition itself refers to the process of returning a suspect who has committed a crime abroad and wishes to return to his or her home country. The extradition case against Djoko Tjandra is therefore itself an example of extradition practice. The arrest and custody of Djoko S. Tjandra was made possible through the cooperation of the National Police and the Royal Malaysian Police. Kabareskrim Polri Argo Yuwono confirmed that the national police will make arrests, which has proven the existence of